Islamic Global Leadership Model: Integration of Global Competence and Akhlaq Competence - Rahman El Junusi; Olivia Fachrunnisa; Tri Wikaningrum; Bambang Widarno (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The rapid flow of globalization demands global leadership at all levels of the organization to have the skills and competencies to succeed in a global environment. The field of study of global leadership has experienced rapid development, but it is still faced with several problems, namely the absence of universal consensus regarding the concept of global leadership and what global leadership competencies are needed, to successfully manage organizations in a global environment. So far, the development of global leadership has focused on global competence, while moral competence has received little attention. To build global leadership, we intervene in global leadership with Islamic moral values or akhlaq, which results in a new or novel concept, namely Islamic global leadership (IGL). Therefore, this article aims to conceptualize IGL and its competencies. This concept is expected to be able to give a new color to the development of global leadership in theory and practice.